2010
DOI: 10.1007/s10549-010-0909-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel BRCA1 nucleotide 4803delCC/c.4684delCC mutation and a nucleotide 249T>A/c.130T>A (p.Cys44Ser) mutation in two Greenlandic Inuit families: implications for genetic screening of Greenlandic Inuit families with high risk for breast and/or ovarian cancer

Abstract: Germ-line mutations in the tumour suppressor proteins BRCA1 and BRCA2 predispose to breast and ovarian cancer. We have recently identified a Greenlandic Inuit BRCA1 nucleotide 234T>G/c.115T>G (p.Cys39Gly) founder mutation, which at that time was the only disease-causing BRCA1/BRCA2 mutation identified in this population. Here, we describe the identification of a novel disease-causing BRCA1 nucleotide 4803delCC/c.4684delCC mutation in a Greenlandic Inuit with ovarian cancer. The mutation introduces a frameshift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
4
13
0
Order By: Relevance
“…In this study a disease-causing point mutation in the BRCA1 gene was identified in a Greenlandic Inuit with ovarian cancer (Hansen et al 2010). It was the first report of this specific point mutation in the Greenlandic Inuit population, but the same point mutation had previously been observed among four Danes with breast and/or ovarian cancer.…”
Section: Applications To Analyses Of Disease-related Mutationssupporting
confidence: 53%
See 4 more Smart Citations
“…In this study a disease-causing point mutation in the BRCA1 gene was identified in a Greenlandic Inuit with ovarian cancer (Hansen et al 2010). It was the first report of this specific point mutation in the Greenlandic Inuit population, but the same point mutation had previously been observed among four Danes with breast and/or ovarian cancer.…”
Section: Applications To Analyses Of Disease-related Mutationssupporting
confidence: 53%
“…The first data set consists of five patients with breast and/or ovarian cancer, four Danes and one Greenlandic Inuit. These individuals are all heterozygous for a recently identified mutation in their BRCA1 gene on chromosome 17 (Hansen et al 2010). Except for two of the individuals that have a coancestry coefficient of 0.107, the individuals are seemingly unrelated (the remaining coancestry coefficients are all lower than 0.014).…”
Section: Real Test Datamentioning
confidence: 99%
See 3 more Smart Citations